Parallel Programming, Models and Applications in Grid and P2P Systems - Xhafa, Fatos (IOS Press, 2013)
This book series publishes research and development results on all aspects of parallel computing. Topics may include one or more of the following: high-speed computing architectures (Grids, clusters, Service Oriented Architectures, etc.), network technology, performance measurement, system software, middleware, algorithm design, development tools, software engineering, services and applications